Carfilzomib modulates tumor microenvironment to potentiate immune checkpoint therapy for cancer - Zhou, Qian; Liang, Jinxia; Yang, Tong; Liu, Jin; Li, Bo; Li, Yingchang; Fan, Zhenzhen; Wang, Weida; Chen, Wensheng; Yuan, Sujing; Xu, Meng; Xu, Qigui; et al. (EMBO molecular medicine, 2022)
Impressive clinical benefit is seen in clinic with PD‐1 inhibitors on portion of cancer patients. Yet, there remains an urgent need to develop effective synergizers to expand their clinical application. Tumor‐associated macrophage (TAM), a type of M2‐polarized macrophage, eliminates or suppresses T‐cell‐mediated anti‐tumor responses. Transforming TAMs into M1 macrophages is an attractive strategy of anti‐tumor therapy. Here, we conducted a high‐throughput screening and found that Carfilzomib potently drove M2 macrophages to express M1 cytokines, phagocytose tumor cells, and present antigens to T cells. Mechanistically, Carfilzomib elicited unfolded protein response (UPR), activated IRE1α to recruit TRAF2, and activated NF‐κB to transcribe genes encoding M1 markers in M2 macrophages. In vivo , Carfilzomib effectively rewired tumor microenvironment through reprogramming TAMs into M1‐like macrophages and shrank autochthonous lung cancers in transgenic mouse model. More importantly, Carfilzomib synergized with PD‐1 antibody to almost completely regress autochthonous lung cancers. Given the safety profiles of Carfilzomib in clinic, our work suggested a potentially immediate application of combinational treatment with Carfilzomib and PD‐1 inhibitors for patients with solid tumors. Synopsis Tumor‐associated macrophages (TAMs) are highly immunosuppressive. A high‐throughput drug screening was performed to identify FDA‐approved drugs that can reprogram TAMs into immunostimulatory M1 macrophages. Carfilzomib, together with two other protease inhibitors, was identified as capable of reprogramming M2 into M1 macrophages. ER stress‐IRE1a‐TRAF2‐NF‐kappa B axis was found responsible for the reprogramming. Carfilzomib treatment effectively shrinks autochthonous lung cancers in a transgenic mouse model. Carfilzomib synergized with PD‐1 antibody to completely regress autochthonous lung cancers in mice. Graphical Abstract Tumor‐associated macrophages (TAMs) are highly immunosuppressive. A high‐throughput drug screening was performed to identify FDA‐approved drugs that can reprogram TAMs into immunostimulatory M1 macrophages.